Hirudin ameliorates immunoglobulin A nephropathy by inhibition of fibrosis and inflammatory response. (1st January 2019) - Deng, Fei; Zhang, Jingwei; Li, Yi; Wang, Wei; Hong, Daqing; Li, Guisen; Feng, Jing
Abstract: Immunoglobulin A nephropathy (IgAN) is characterized by mesangial IgA and IgG co-deposition. As the clinical course of IgAN is highly variable, a lot of patients will eventually develop to end-stage renal disease (ESRD) within years. Hirudin, a potent and specific thrombin inhibitor, has been reported to treat IgAN with hematuria, but the mechanism is unclear. Our study aims to explore the potential of hirudin and the underlying mechanism in the treatment of IgAN. The establishment of IgAN model was set up in rats through oral and intravenous immunization with bovine gamma-globulin (BGG). Results suggested that hirudin could reduce the increased level of proteinuria, serum creatinine and urea nitrogen in IgAN models. Besides that, hirudin ameliorated the elevated number of apoptotic bodies and expressions of apoptosis-related proteins (caspase-3 and caspase-9) in IgAN model. The fibrosis indexes (transforming growth factor β-1 (TGF-β1), Collagen-IV (CoI-IV) and Fibronectin-1) of kidney were remarkably suppressed in IgAN rats treated with hirudin compared with IgAN rats with no further treatment. IgAN rats exhibited remarkably increased inflammatory factors (IL-1β, IL-6, and IL-18), while hirudin treatment significantly alleviated these alterations. Moreover, the reduced levels of CD4 + CD25 + Foxp3 + Treg and CD4 + IFN-γ + Th1/CD4 + IL-4 + Th2 could be reversed by hirudin in IgAN model. Furthermore, in the process of IgAN, hirudin could inactivate various pathways (IκBα, NF-κB, TNF-α, and VCAM-1) compared with IgAN model group. Taken together, our study indicated that hirudin could ameliorate IgAN through suppressing fibrosis and inflammatory response. These findings provide a new therapeutic method to treat IgAN.